2010
DOI: 10.1021/ol102289g
|View full text |Cite
|
Sign up to set email alerts
|

Highly Diastereo- and Enantioselective Organocatalytic Michael Addition of α-Ketoamides to Nitroalkenes

Abstract: The first organocatalytic enantio- and diastereoselective conjugate addition of α-ketoamides to nitroalkenes has been achieved using a bifunctional amino thiourea catalyst. In this new approach, the substrate amide proton plays a critical role in the formation of the Michael anti-adducts in high yields and high stereoselectivities. To illustrate the high synthetic potential of this methodology, the diastereo- and enantioselective synthesis of a hexasubstituted cyclohexane via a Michael-Michael-Henry cascade re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(40 citation statements)
references
References 67 publications
1
38
0
1
Order By: Relevance
“…[154] These products with all-cis stereochemistry were generated from the reaction of nitroalkenes, a,b-unsaturated aldehydes, and stabilized Wittig reagent 336, upon catalysis with chiral amine (S)-3 in the presence of acetic acid. Excellent enantioselectivities of up to 99% ee were achieved in combination with moderate to good yields (34-59%) and low to moderate diastereoselectivities (0-34% de), as shown in Scheme 88.…”
Section: Michael Reaction Of Nitroolefinsmentioning
confidence: 99%
See 1 more Smart Citation
“…[154] These products with all-cis stereochemistry were generated from the reaction of nitroalkenes, a,b-unsaturated aldehydes, and stabilized Wittig reagent 336, upon catalysis with chiral amine (S)-3 in the presence of acetic acid. Excellent enantioselectivities of up to 99% ee were achieved in combination with moderate to good yields (34-59%) and low to moderate diastereoselectivities (0-34% de), as shown in Scheme 88.…”
Section: Michael Reaction Of Nitroolefinsmentioning
confidence: 99%
“…In 2010, Rodriguez et al reported an enantioselective synthesis of polyfunctionalized hexasubstituted cyclohexane 339 through a three-component domino Michael-Michael-Henry-type reaction catalyzed by chiral bifunctional amine thiourea (R,R)-41. [154] In this process, two equivalents of a nitroalkene reacted with a-ketoanilide 340 to give the product bearing six contiguous stereogenic centers in 61% yield and excellent diastereo-and enantioselectivity of > 90% de and 98% ee, respectively, as shown in Scheme 89.…”
Section: Michael Reaction Of Nitroolefinsmentioning
confidence: 99%
“…[4][5][6] In particular, bifunctional amine-thiourea-based catalysts have proved to be efficient in various asymmetric transformations owing to the ability of the thiourea moiety to highly activate carbonyl or nitro groups through double hydrogenbonding interactions. 7,8 Therefore, this kind of organocatalyst has been widely studied in [12][13][14][15][16][17][18][19][20][21][22] Since Tsogoeva 23 and Jacobsen 24 demonstrated that a primary amine-thiourea catalyst can act as efficient bifunctional catalyst for the asymmetric nitro Michael addition, such bifunctional organocatalysts have attracted much attention owing to their easy preparation from chiral diamines. [25][26][27][28][29][30][31][32] However, the chiral scaffold of these reported organocatalysts is limited and is mostly derived from 1,2-diaminocyclohexane and 1,2-phenylethylenediamine.…”
Section: Introductionmentioning
confidence: 99%
“…The interest in asymmetric organocatalysis [1][2][3][4][5][6][7][8][9][10][11][12] has rapidly increased since the pioneering works of List, Barbas, and their coworkers in 2001. 13,14 The reactions between carbonyl compounds and nitroolefins have been among the most studied reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33][34][35] However, while several examples are reported on organocatalyzed conjugated addition of 1,3-dicarbonyl compounds to nitroalkenes, [36][37][38][39][40][41][42][43][44] only a few cases can be found in the literature regarding the same reaction with 1,2-dicarbonyl compounds, 7,45,46 namely with 1,2-cyclohexanedione 45,46 and a-ketoanilides. 7 Several years ago, [47][48][49] (S)-(À)-1-phenylethylimine 2 derived from 2,3-butanedione 1 and (S)-(À)-1-phenylethylamine (Scheme 1) has been found to react with cyclic and acyclic nitroolefins 3a-d, both in solvent and under solvent-free conditions, to give products of carbocyclization reactions (À)-4a-d. The imine intermediates (À)-4b-d were converted into the corresponding a-ketols (+)-5b-d, either by acid hydrolysis under mild conditions or by oxidation of the C¼N bond followed by acidic treatment.…”
Section: Introductionmentioning
confidence: 99%